Influenza H3 hemagglutinin vaccine with scrambled immunodominant epitopes elicits antibodies directed toward immunosubdominant head epitopes - Shiho Chiba; Huihui Kong; Gabriele Neumann; Yoshihiro Kawaoka (mBio, 2023)
ABSTRACT Vaccination is the most effective countermeasure to reduce the severity of influenza. Current seasonal influenza vaccines mainly elicit humoral immunity targeting hemagglutinin (HA). In particular, the amino acid residues around the receptor-binding site in the HA head domain are predominantly targeted by humoral immunity as “immunodominant” epitopes. However, mutations readily accumulate in the head domain due to high plasticity, resulting in antigenic drift and vaccine mismatch, particularly with influenza A (H3N2) viruses. A vaccine strategy that targets more conserved immunosubdominant epitopes is required to attain a universal vaccine. Here, we designed an H3 HA vaccine antigen with various amino acids at immunodominant epitopes of the HA head domain, termed scrambled HA (scrHA). In ferrets, scrHA vaccination induced lower serum neutralizing antibody levels against homologous virus compared with wild-type (WT) HA vaccination; however, similar levels of moderately neutralizing titers against antigenically distinct H3N2 viruses were observed. Ferrets vaccinated with scrHA twice and then challenged with homologous or heterologous virus showed the same level of reduced virus shedding in nasal swabs as WT HA-vaccinated animals but reduced body temperature increase, whereas WT HA-vaccinated ferrets exhibited body temperature increases similar to those of mock-vaccinated animals. scrHA elicited antibodies against HA immunodominant and -subdominant epitopes at lower and higher levels, respectively, than WT HA vaccination, whereas antistalk antibodies were induced at the same level for both groups, suggesting scrHA-induced redirection from immunodominant to immunosubdominant head epitopes. scrHA vaccination thus induced broader coverage than WT HA vaccination by diluting out the immunodominancy of HA head epitopes. IMPORTANCE Current influenza vaccines mainly elicit antibodies that target the immunodominant head domain, where strain-specific mutations rapidly accumulate, resulting in frequent antigenic drift and vaccine mismatch. Targeting conserved immunosubdominant epitopes is essential to attain a universal vaccine. Our findings with the scrHA developed in this study suggest that designing vaccine antigens that “dilute out” the immunodominancy of the head epitopes may be an effective strategy to induce conserved immunosubdominant epitope-based immune responses.